Melanopsin Driven Light Responses Across a Large Fraction of Retinal Ganglion Cells in a Dystrophic Retina - Eleftheriou, Cyril G.; Wright, Phillip; Allen, Annette E.; Elijah, Daniel; Martial, Franck P.; Lucas, Robert J. (Frontiers in Neuroscience, 2020)
Intrinsically photosensitive retinal ganglion cells (ipRGCs) express the photopigment melanopsin and project to central targets, allowing them to contribute to both image-forming and non-image forming vision. Recent studies have highlighted chemical and electrical synapses between ipRGCs and neurons of the inner retina, suggesting a potential influence from the melanopsin-born signal to affect visual processing at an early stage of the visual pathway. We investigated melanopsin responses in ganglion cell layer (GCL) neurons of both intact and dystrophic mouse retinas using 256 channel multi-electrode array (MEA) recordings. A wide 200 µm inter-electrode spacing enabled a pan-retinal visualization of melanopsin’s influence upon GCL activity. Upon initial stimulation of dystrophic retinas with a long, bright light pulse, over 37% of units responded with an increase in firing (a far greater fraction than can be expected from the anatomically characterised number of ipRGCs). This relatively widespread response dissipated with repeated stimulation even at a quite long inter-stimulus interval (120s), to leave a smaller fraction of responsive units (<10%; more in tune with the predicted number of ipRGCs). Visually intact retinas appeared to lack such widespread melanopsin responses indicating that it is a feature of dystrophy. Taken together our data reveal the potential for anomalously widespread melanopsin responses in advanced retinal degeneration. These could be used to probe the functional reorganisation of retinal circuits in degeneration and should be taken into account when using retinally degenerate mice as a model of disease.